2020
DOI: 10.3389/fnins.2020.509364
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Kinematic Information From Primary Motor Cortex Ensemble Activities Using a Deep Canonical Correlation Analysis

Abstract: The control of arm movements through intracortical brain-machine interfaces (BMIs) mainly relies on the activities of the primary motor cortex (M1) neurons and mathematical models that decode their activities. Recent research on decoding process attempts to not only improve the performance but also simultaneously understand neural and behavioral relationships. In this study, we propose an efficient decoding algorithm using a deep canonical correlation analysis (DCCA), which maximizes correlations between canon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In addition, unlike what the second stage of RNN PSID enables, these prior works do not model additional neural dynamics beyond those that decode behavior, and thus do not aim to dissociate the two types of neural dynamics. Moreover, each of these works 15,16 , including those with non-causal sequential autoencoders 2 , use specific nonlinear RNN structures whereas in RNN PSID the nonlinear structure is automatically selected in a way that best suits the training data within an inner cross-validation (Methods). Finally, importantly, here unlike prior works, we further dissect the nonlinearity and explore how one can isolate the nonlinearity in specific parameters of the nonlinear RNN, each of which has interpretable roles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, unlike what the second stage of RNN PSID enables, these prior works do not model additional neural dynamics beyond those that decode behavior, and thus do not aim to dissociate the two types of neural dynamics. Moreover, each of these works 15,16 , including those with non-causal sequential autoencoders 2 , use specific nonlinear RNN structures whereas in RNN PSID the nonlinear structure is automatically selected in a way that best suits the training data within an inner cross-validation (Methods). Finally, importantly, here unlike prior works, we further dissect the nonlinearity and explore how one can isolate the nonlinearity in specific parameters of the nonlinear RNN, each of which has interpretable roles.…”
Section: Discussionmentioning
confidence: 99%
“…In equation (16), each multiplication between a model parameter and a vector (e.g. ′ ) can be thought of as a multi-input-multi-output linear function applied to an input vector (e.g.…”
Section: /56mentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, DCCA, which finds optimal parameters to maximize the correlation between latent variables for two random variables is often used for different purposes other than MLP or LSTM [27]. Kim et al showed the effects of latent variables extracted by DCCA on motor decoding performance, where the two random variables correspond to firing rates and kinematic variables [29]. This examined the feasibility of motor decoding with DCCA structure-extracting latent variables by directly associating neuronal population activity with kinematic variables.…”
Section: Introductionmentioning
confidence: 99%